Compartmentalised cAMP signalling in the primary cilium - Paolocci, Ester; Zaccolo, Manuela (Frontiers in Physiology, 2023)
cAMP is a universal second messenger that relies on precise spatio-temporal regulation to control varied, and often opposing, cellular functions. This is achieved via selective activation of effectors embedded in multiprotein complexes, or signalosomes, that reside at distinct subcellular locations. cAMP is also one of many pathways known to operate within the primary cilium. Dysfunction of ciliary signaling leads to a class of diseases known as ciliopathies. In Autosomal Dominant Polycystic Kidney Disease (ADPKD), a ciliopathy characterized by the formation of fluid-filled kidney cysts, upregulation of cAMP signaling is known to drive cystogenesis. For decades it has been debated whether the primary cilium is an independent cAMP sub-compartment, or whether it shares a diffusible pool of cAMP with the cell body. Recent studies now suggest it is a specific pool of cAMP generated in the cilium that propels cyst formation in ADPKD, supporting the notion that this antenna-like organelle is a compartment within which cAMP signaling occurs independently from cAMP signaling in the bulk cytosol. Here we present examples of cAMP function in the cilium which suggest this mysterious organelle is home to more than one cAMP signalosome. We review evidence that ciliary membrane localization of G-Protein Coupled Receptors (GPCRs) determines their downstream function and discuss how optogenetic tools have contributed to establish that cAMP generated in the primary cilium can drive cystogenesis.